Source apportionment of fine and coarse particles at a roadside and urban background site in London during the 2012 summer ClearfLo campaign. (January 2017) - Crilley, Leigh R.; Lucarelli, Franco; Bloss, William J.; Harrison, Roy M.; Beddows, David C.; Calzolai, Giulia; Nava, Silvia; Valli, Gianluigi; Bernardoni, Vera; Vecchi, Roberta
Abstract: London, like many major cities, has a noted air pollution problem, and a better understanding of the sources of airborne particles in the different size fractions will facilitate the implementation and effectiveness of control strategies to reduce air pollution. Thus, the trace elemental composition of the fine and coarse fraction were analysed at hourly time resolution at urban background (North Kensington, NK) and roadside (Marylebone Road, MR) sites within central London. Unlike previous work, the current study focuses on measurements during the summer providing a snapshot of contributing sources, utilising the high time resolution to improve source identification. Roadside enrichment was observed for a large number of elements associated with traffic emissions (Al, S, Ca, Ti, V, Cr, Mn, Fe, Ni, Cu, Zn, As, Rb and Zr), while those elements that are typically from more regional sources (e.g. Na, Cl, S and K) were not found to have an appreciable increment. Positive Matrix Factorization (PMF) was applied for the source apportionment of the particle mass at both sites with similar sources being identified, including sea salt, airborne soil, traffic emissions, secondary inorganic aerosols and a Zn-Pb source. In the fine fraction, traffic emissions was the largest contributing source at MR (31.9%), whereas it was incorporated within an "urban background" source at NK, which had contributions from wood smoke, vehicle emissions and secondary particles. Regional sources were the major contributors to the coarse fraction at both sites. Secondary inorganic aerosols (which contained influences from shipping emissions and coal combustion) source factors accounted for around 33% of the PM10 at NK and were found to have the highest contributions from regional sources, including from the European mainland. Exhaust and non-exhaust sources both contribute appreciably to PM10 levels at the MR site, highlighting the continuing importance of vehicle-related air pollutants at roadside. Highlights: Hourly elemental composition of fine and coarse fraction measured during summer. Improved source apportionment by PMF compared to previous work in London. Sources included marine, soil, traffic, secondary inorganic, construction, Zn-Pb. Regional sources were major contributors to the coarse fraction at both sites. Shipping and industrial emissions have significant impact upon secondary aerosol. Abstract : Trace element composition of airborne particles in London reveals major contributions from regional (including shipping and industry) and local sources (road traffic and construction).